Teologia nauki – propozycja nowego otwarcia teologii na nauki - Trombik, Kamil; Polak, Paweł (Człowiek i Społeczeństwo, 2022)
In this paper we discuss the idea of theology of science, which is understood as a new branch of the- ology concerned with the problems arising in the context of natural sciences. Theology of science has been developed since 1980s. The authors of this concept are Michał Heller and Józef Życiński – philosophers involved in discussions between science and religion, who tried to find a new common area to develop this dialogue. The aim of the paper is to present the concept of theology of science in the historical and problematic perspective, taking into account the various challenges and research perspectives faced by this concept.